Pregnancy outcomes and early infancy physical growth of fetal situs inversus during the COVID-19 pandemic - Zhang, Yongke; Dong, Xingsheng; Li, Haijun; Chen, Ran; Cai, Fenge; Zhang, Dirong (Frontiers in Medicine, 2025)
ObjectiveThis research aimed to observe the pregnancy outcomes and early infancy physical growth of fetuses with situs inversus detected during the coronavirus disease 2019 (COVID-19) pandemic at two centers in South China.MethodsData were collected from pregnant women with fetal situs inversus between March 2023 and May 2024. Systemic structured ultrasound, clinical manifestations, and genetic tests were conducted. Data on pregnancy outcomes and routine physical examinations of neonates and infants were collected. Statistical analysis was performed to compare the incidence rate of fetal situs inversus in 2023 with the median incidence rate in previous years. Z-scores for head circumference, weight, and length of the infants were calculated using PediTools Electronic Growth Chart Calculators.ResultsA total of 27 patients with fetal situs inversus were detected; situs inversus with dextrocardia was the most common category of all cases (23/27, 85.2%). The incidence rate of fetal situs inversus in Center 1 increased more than sixfold in 2023 compared with the median incidence rate of previous years (1.75‰ vs. 0.25‰, p = 0.000), while in Center 2, the increase was not so obvious (1.22‰ vs. 0.51‰, p = 0.011), both with the peak number of affected fetuses detected mainly in April 2023. In total, 15 newborns with situs inversus totalis (SIT) were delivered (15/27, 55.6%), and the majority were alive and reached their normal growth milestones, except for one infant death. Overall, 11 pregnancies underwent therapeutic abortion, and 1 pregnant woman received twin reduction surgery for one of the cotwins (12/27, 44.4%). Z-score evaluation showed no abnormal early physical growth in weight, head circumference, or length among infants with SIT.ConclusionA high incidence of fetal situs inversus during the COVID-19 pandemic was observed in our study. Situs inversus with dextrocardia was associated with relatively good pregnancy outcomes in non-complicated cases. No abnormal early infancy physical growth in weight, head circumference, or length was observed among infants with SIT.